Flavivirus NS1 Triggers Tissue-Specific Vascular Endothelial Dysfunction Reflecting Disease Tropism - Puerta-Guardo, Henry (Cell Rep, 2019)
Flaviviruses cause systemic or neurotropic-encephalitic pathology in humans. The flavivirus nonstructural protein 1 (NS1) is a secreted glycoprotein involved in viral replication, immune evasion, and vascular leakage during dengue virus infection. However, the contribution of secreted NS1 from related flaviviruses to viral pathogenesis remains unknown. Here, we demonstrate that NS1 from dengue, Zika, West Nile, Japanese encephalitis, and yellow fever viruses selectively binds to and alters permeability of human endothelial cells from lung, dermis, umbilical vein, brain, and liver in vitro and causes tissue-specific vascular leakage in mice, reflecting the pathophysiology of each flavivirus. Mechanistically, each flavivirus NS1 leads to differential disruption of endothelial glycocalyx components, resulting in endothelial hyperpermeability. Our findings reveal the capacity of a secreted viral protein to modulate endothelial barrier function in a tissue-specific manner both in vitro and in vivo, potentially influencing virus dissemination and pathogenesis and providing targets for antiviral therapies and vaccine development.